Moral Compass for the Digital Future: A Philosophical-Educational Framework in Society 5.0 - Rahmelia, Vivi; Munawarah; Sudrajat; Wulandari, Taat (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2026)
The rapid advancement of technology in the society 5.0 era presents opportunities and challenges, particularly in shaping ethical behavior and social responsibility. This study explores how integrating the philosophy of science with character education can strengthen moral formation amid these changes. Using a qualitative literature review, it analyzes scholarly sources on philosophy of science, character education, and digital-era morality. The findings show that the philosophy of science offers a framework for ethical and critical thinking, while character education provides practical pathways to internalize and apply these values. Unlike previous studies that address them separately, this research highlights their integration as a strategy to align technological competence with ethical responsibility. Embedding philosophical principles into character education encourages students to develop cognitive, technical, and moral capacities simultaneously. This synergy can inform curriculum design, teacher training, and digital literacy programs, ultimately fostering ethically grounded digital citizens who are prepared to navigate the complexities of society 5.0.